A COMPARATIVE STUDY OF ENGLISH AND MANDARIN LITERARY THEORY AND CRITICISM: CROSS CULTURAL PERSPECTIVES ON LANGUAGE, INTERPRETATION, AESTHETICS, AND IDEOLOGICAL DISCOURSE - Devi Devi Alvionita Alindra; M. Manugeren; Saiful Anwar Matondang (English Language Teaching Prima Journal (ELT), 2026)
Literary theory and criticism are essential for understanding how literary texts are interpreted, evaluated, and connected to cultural and ideological contexts. In comparative literature, English and Mandarin literary criticism represent two major traditions shaped by different philosophical, linguistic, and historical backgrounds. English literary theory has been influenced by Greco-Roman philosophy, Enlightenment rationalism, structuralism, psychoanalysis, feminism, post-structuralism, and postcolonial studies, emphasizing critical inquiry, textual plurality, and the questioning of authority. Conversely, Mandarin literary criticism is grounded in Confucianism, Daoism, Buddhism, and classical Chinese poetics, focusing on moral cultivation, social harmony, symbolic expression, and historical continuity. This study examines the similarities and differences between these traditions by analyzing their philosophical foundations, interpretive methods, narrative structures, and ideological functions. Employing a qualitative comparative approach, the research integrates hermeneutic textual analysis, discourse analysis, and cross-cultural interpretation. The findings indicate that English criticism tends to prioritize analytical interpretation and multiple meanings, while Mandarin criticism emphasizes holistic understanding and ethical relationships. Furthermore, globalization and intercultural exchanges have increasingly connected these traditions, enriching literary studies and broadening perspectives on culture, identity, and human consciousness.